Cybersecurity of Operational Technology in Critical Infrastructures (Belügyi Szemle, 2025)
Aim: The aim of this study is to present the relationship between critical infrastructures and operational technology (OT) and to explore the cybersecurity challenges arising from the integration of IT and OT systems. The central research question is: What are the main vulnerabilities that emerge in critical infrastructures due to the interconnection of OT and IT systems, and what defense strategies can mitigate these risks?Methodology: The research adopts an interdisciplinary approach that combines theoretical-logical analysis, literature review, case study analysis, and the examination of practical examples. The following hypotheses were investigated:H1: The convergence of IT and OT systems results in an increased attack surface, as OT systems become vulnerable through IT networks.H2: The security mechanisms applied in critical infrastructures do not always meet the specific security requirements of OT, increasing system vulnerabilities.H3: Proper segmentation strategies and the establishment of controlled communication channels between IT and OT networks can reduce the risk of cyberattacks.The research also includes comparative analyses examining security measures applied in industrial and critical infrastructure settings. To gain a deeper understanding of the cybersecurity challenges of OT systems, industry reports and case studies were also analysed.Findings: The protection of operational technology systems in critical infrastructures is crucial for maintaining social and economic stability. The digitalization of OT systems and their increasing integration with IT systems create new cybersecurity challenges that require a complex and multi-layered approach to address. The study highlights that proper segmentation and secure interconnection of IT and OT systems are key to effectively managing cyber threats.Value: This research provides a comprehensive overview of the cybersecurity challenges associated with operational technology, with a particular focus on critical infrastructures. It offers valuable guidance for developing defense strategies from both scientific and practical perspectives, supporting the secure integration of IT and OT systems.